MODELING OF SUPPLY AND DEMAND FOR MAIZE IN KILIFI DISTRICT, KENYA: A COBWEB MODEL APPROACH - Ronald, Koech; Willy-Marcel, Ndayitwayeko; Charles, Karani (IJRDO - Journal of Business Management, 2018)
The study aimed at assessing the determinants of demand and supply of maize in Kilifi, Kenya using the cobweb model for analysis. Results showedthat variations in production of maize were explained by the prices of cassava, income per capita of consumers and time trend. Price of cassava (maize substitute) werestrongly significant (p<0.01) and had expected negative sign. This implied that if the price of cassava increased, farmers would shift from maize production to cassava production. In the model, an increase of price of a bag of cassava by 1 US would decrease the production of maize by 0.95 per cent in the long-run. Income per capita of consumers was significant (p<0.1) though with unexpected sign. The study established that there is need for intensification of maize production due to its importance through provision of the prerequisite incentives such as extension and inputs.